New Look at the Origin of the Sumba Terrane: Multidisiplinary Approaches - Satyana, Awang H.; Purwaningsih, Margaretha E. M. (Berita Sedimentologi, 2012)
Sumba Island belongs to the Lesser Sunda Islands Group. Geologically, the island is located in a forearc setting in front of the Quaternary Sunda-Banda volcanic arcs, which comprise the islands of Bali-Lombok-Sumbawa-Flores-Alor and Wetar. Sumba Island is presently non-volcanic and is tectonically important since it is located at the border of subduction and collision zones. To the west of Sumba, oceanic crust of the Indian Ocean is being subducted beneath the Sunda Arc. To the east of Sumba, there is collision zone where Australian continental crust underthrusts Timor Island.Based on tectonic studies, Sumba has been considered as a micro-continent or continental fragment/ sliver which detached itself from its provenance and was transported to its present position as an exotic terrane. Gravity data show that Sumba has a gravity anomaly of +160 to +200 mgal and is underlain by continental crust with a thickness of 24 km.The pre-Tertiary basement of Sumba reveals faulting with rifted blocks. Overlying this are Late Cretaceous-Paleocene marine turbidites of the Lasipu Formation. This period is accompanied by two major calc-alkaline magmatic episodes, the Santonian-Campanian episode (86-77 Ma) and the Maastrichtian-Thanetian one (71-56 Ma). Overlying these are volcaniclastic and neritic sediments accompanied by volcanic rocks belonging to theLutetian-Rupelian Paumbapa Formation (42-31 Ma). The Neogene rocks are composed of widespread transgressive and turbiditic chalky sediments of the Kananggar/Sumba Formation, which contain reworked volcanic materials. Synsedimentary tectonism with normal faulting and largescale slumping occurred during the Neogene. The Quaternary rocks are coral reefs, uplifted to form terraces.